Interaction of non-coding RNAs and Hippo signaling: Implications for tumorigenesis. (28th November 2020) - Liu, Can; Wu, Yangge; Ma, Jian
Abstract: Hippo signaling is an evolutionarily conserved pathway that controls organ size by regulating cell proliferation, apoptosis, and stem cell self-renewal by "turning off" or "turning on" the kinase cascade chain reaction to manipulate the expression of downstream genes. Dysregulation of the Hippo pathway contributes to cancer development and metastasis. Emerging evidence has revealed new insights into tumorigenesis through the interplay between the Hippo pathway and non-coding RNAs (ncRNAs), especially microRNA, long non-coding RNA and circular RNA. Here, we reviewed the interactions between the Hippo pathway and ncRNAs and their implication for a variety of tumor-promoting or tumor-repressing effects. These interactions have the potential to serve as cancer biomarkers and therapeutic targets in clinical applications.